Cognitive functions in first degree normative relative of patients with schozophrenia - Chaudhari, Falguni A.; Shah, Parag S.; Deshpandey, Ujjwala (International Journal of Research in Medical Sciences, 2018)
Background: Schizophrenia is severe disorders and imposes a considerable burden on patients, their families and society. Schizophrenia tends to run in family, like most mental disorder shows complex inheritance. Therefore, it is important to increase our knowledge about the disorder. Cognitive dysfunction is one of the core features of Schizophrenia. This study aims to compare the cognitive function of first degree unaffected relative of patient of schizophrenia and a group of healthy control. Methods: The study include 48 first degree normative relative of patient with Schizophrenia and 48 controls. Compared for age, sex, education level. Cognitive functions of each case and control were assessed using TMT (Trail making Test), Paced auditory serial addition Test (PASAT) and Wisconsin card sorting test (WCST-64). Results: First degree relative performed significantly poorly as compared to controls on Wisconsin card sorting Test-64 (WCST-64). No significant difference was observed in tests performances between first degree relative of Schizophrenia and control group for TMT (trail making test) and Paced auditory serial addition Test (PASAT). Conclusions: The study shows possibility of cognitive impairment in first degree normative relative of Schizophrenia with regards to parameters like poor performance in shifting cognitive sets and poor understanding of test. Nevertheless, it is not clear weather this finding is an enduring trait mark or finding that fluctuates with sample size, nature of case and control.